2017
DOI: 10.1186/s12909-017-0917-0
|View full text |Cite
|
Sign up to set email alerts
|

Norwegian midwives’ opinion of their midwifery education – a mixed methods study

Abstract: BackgroundMidwifery education in Norway has undergone radical reforms in the past few decades. In 2004, the compulsory year of paid internship was removed from the requirement to become an authorised midwife. Since then, authorisation as a midwife depends on the successful completion of a two-year full-time academic course, consisting of 50% clinical practice and 50% theoretical education. Our objective was to examine midwives’ opinion of their Norwegian midwifery education in relation to their midwifery pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…In British Columbia, the Netherlands, New Zealand, and Ontario, basic midwifery education requires completion of a 4‐year, direct‐entry, baccalaureate degree in midwifery . In Iceland, Japan, Norway, and Sweden, students complete a baccalaureate nursing degree and then postgraduate studies in midwifery or nurse‐midwifery—further details are provided in Table . Australia, England, and Washington State have multiple educational pathways.…”
Section: Resultsmentioning
confidence: 99%
“…In British Columbia, the Netherlands, New Zealand, and Ontario, basic midwifery education requires completion of a 4‐year, direct‐entry, baccalaureate degree in midwifery . In Iceland, Japan, Norway, and Sweden, students complete a baccalaureate nursing degree and then postgraduate studies in midwifery or nurse‐midwifery—further details are provided in Table . Australia, England, and Washington State have multiple educational pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Lukasse et al showed that many midwives have a negative view to midwifery instructors who have not been in clinical practice for many years or who are not up-to-date in clinical practice. Old and outdated teaching methods lead to a gap between theory and practice [42].…”
Section: Discussionmentioning
confidence: 99%
“…High-quality patient care is only feasible if midwives have received high-quality teaching during their course of study and working years. Current education methods related to the theoretical and practical training of midwives can help them to recognize and manage better patients' needs by means of simulated cases 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Simulation-based education can create a specific learning environment to ensure midwifery students manage their experiential learning by reinforcing clinical skills through different levels of competency. In both undergraduate teaching and post-registration education, simulation is increasingly being used as a teaching tool within midwifery to teach both emergency situations and practice skills 5,6 .…”
Section: Introductionmentioning
confidence: 99%